Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1136/jmg.40.8.585
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary haemorrhagic telangiectasia: a questionnaire based study to delineate the different phenotypes caused by endoglin and ALK1 mutations

Abstract: Background: Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant vascular dysplasia characterised by mucocutaneous telangiectasis, epistaxis, gastrointestinal haemorrhage, and arteriovenous malformations in the lung and brain. Causative mutations for HHT have been identified in two genes, endoglin and ALK1, which encode proteins involved in serine-threonine kinase signalling in the endothelial cell. Methods: A number of people affected with HHT had completed a postal questionnaire as part of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
124
3
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(149 citation statements)
references
References 38 publications
10
124
3
9
Order By: Relevance
“…In that study, an earlier onset of epistaxis and telangiectasis was present in patients with HHT1. In addition, pulmonary arteriovenous malformations (PAVM) were only seen in HHT1 (Berg et al, 2003), which confirmed earlier observations . However, PAVMs can also be encountered in some patients with HHT2 (McDonald et al, 2000;Kjeldsen et al, 2001).…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…In that study, an earlier onset of epistaxis and telangiectasis was present in patients with HHT1. In addition, pulmonary arteriovenous malformations (PAVM) were only seen in HHT1 (Berg et al, 2003), which confirmed earlier observations . However, PAVMs can also be encountered in some patients with HHT2 (McDonald et al, 2000;Kjeldsen et al, 2001).…”
Section: Introductionsupporting
confidence: 90%
“…Fifty seven mutations were listed in the recent review by van den Driesche and colleagues (van der Driesche et al, 2003) while 59 further novel mutations have been published subsequently as follows: 31 mutations (Lesca et al, 2004), 17 (Cymerman et al, 2003), 4 (Lastella et al, 2003), 4 (Berg et al, 2003), 2 (Harrison et al, 2003), and 1 (Chaouat et al, 2004). Together with the one novel ENG mutation detected in this study, the total number of ENG mutations is now 117.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations